Regrowth and catalytic etching of individual single-walled carbon nanotubes studied by isotope labeling and growth interruption. (December 2019) - Koyano, Bunsho; Inoue, Taiki; Yamamoto, Shun; Otsuka, Keigo; Xiang, Rong; Chiashi, Shohei; Maruyama, Shigeo
Abstract: To realize the efficient growth of single-walled carbon nanotubes (SWCNTs), the growth mechanism behind catalyst activity and growth rates needs to be elucidated at the single nanotube level. In this study, we synthesized SWCNTs with growth interruption, where only Ar, Ar/H2, or Ar/H2 /H2 O was introduced during a pause in the supply of a carbon source, in order to examine the effects of additive molecules in a chemical vapor deposition process. This interrupted growth was performed in combination with an isotope labeling technique to show the time evolution of individual SWCNT growth. While the introduction of Ar during the growth interruption tended to terminate SWCNT growth, the introduction of Ar/H2 resulted in the regrowth of SWCNTs once ethanol was reintroduced. When interrupted with Ar/H2 /H2 O, SWCNTs were etched catalytically while sliding themselves in the reverse direction of growth and, then, regrew. Raman analysis revealed that the chirality of SWCNTs was preserved even after etching and regrowth. The growth rates of SWCNTs were unchanged before and after the interruption in the case of Ar/H2, but they were increased by a factor of ∼1.7 in the case of Ar/H2 /H2 O. These results provide effective means to maintain the catalyst activity and to enhance growth rates. Graphical abstract: Image 1